2020
DOI: 10.7163/gpol.0160
|View full text |Cite
|
Sign up to set email alerts
|

Long-term landscape dynamics in the depopulated Carpathian Foothills: A Wiar River basin case study

Abstract: Recently, marginal lands have been attracting attention as areas of high cultural and natural value that are undergoing profound, uncontrolled transformations. These changes are seen as a threat to the cohesion and identity of existing landscapes. However, ongoing processes are often difficult to interpret and evaluate without a long-term historical perspective. Here, we focused on understanding the long-term landscape dynamics in the depopulated and economically marginalized Wiar River basin, where 87% of inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…We are aware of only one local case study from the Wiar river basin (230 km 2 ) that made use of military topographic maps 1:25,000 from the 1950s to capture short-term and direct land cover changes following WWII. The authors showed that forest cover increased from 39% in 1936 to 48% in 1958 and linked it with a dramatic population decline resulting from postwar displacements [65]. Nonetheless, the above study, like many others in the Polish Carpathians, used the low resolution 1:100,000 topographic map from the 1930s to show the pre-war land cover.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We are aware of only one local case study from the Wiar river basin (230 km 2 ) that made use of military topographic maps 1:25,000 from the 1950s to capture short-term and direct land cover changes following WWII. The authors showed that forest cover increased from 39% in 1936 to 48% in 1958 and linked it with a dramatic population decline resulting from postwar displacements [65]. Nonetheless, the above study, like many others in the Polish Carpathians, used the low resolution 1:100,000 topographic map from the 1930s to show the pre-war land cover.…”
Section: Discussionmentioning
confidence: 91%
“…In the last few decades, forest expansion after agricultural abandonment was observed in the Swiss mountains [61] and after the collapse of socialism in the Carpathians and postsoviet Russia [62][63][64]. However, forests that developed on abandoned agricultural lands soon after World War II have not been investigated enough, and therefore, the succession processes and patterns of afforestation are still poorly understood (however, see [22,65]).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, vast areas of mountain borderlands least suitable for agriculture became permanently depopulated and abandoned (Bičík & Štěpánek, 1994; Kučera & Chromy, 2012; Soja, 2012). Three rural mountain regions located within the present borders of Poland belong to those depopulated to the greatest extent: the Śnieżnik Massif (in the Sudetes), the Przemyśl Foothills and the Bieszczady Mountains (both in the Carpathians) (Affek et al, 2020; Latocha, 2012; Wolski, 2007). The land of deserted villages usually underwent nationalization and afforestation, though natural secondary succession also ensued.…”
Section: Study Areamentioning
confidence: 99%
“…It is widely accepted that the analysis of alterations in land cover since the pre-industrial era could reveal pivotal events in Land Use and Land Cover (LULC) changes, particularly evident in the context of long-term change studies derived from topographical sources 7 , 8 . The analysis of LULC changes holds significance as it serves as a vital indicator required for the realization of the United Nations' Sustainable Development Goals (SDGs) 9 11 .…”
Section: Introductionmentioning
confidence: 99%